2005
DOI: 10.1007/s00535-005-1684-y
|View full text |Cite
|
Sign up to set email alerts
|

Primary undifferentiated spindle-cell carcinoma of the gallbladder presenting as a liver tumor

Abstract: Undifferentiated spindle-cell carcinoma (SpCC) of the gallbladder is extremely rare. There is very little information available regarding the characteristics and treatment of this disease. We herein report the unique case of a 76-year-old female patient with a primary SpCC of the gallbladder that presented as a liver tumor. Preoperative radiologic examinations showed a 5-cm liver tumor around the gallbladder bed, and irregular thickening of the gallbladder wall. The patient underwent en-bloc resection of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
1
12
0
3
Order By: Relevance
“…The results of the analysis, which are shown in Table I, showed that the patients' mean age was 66.6 years and that a high percentage of affected patients were female (female-to-male ratio, 1.57-7.00). Of note, in group A, the prognostic data in more recent studies (5-7) tended to be improved compared with those in earlier studies (2)(3)(4). Among the more recent studies, no significant difference between the prognostic data in groups A (5-7) and B (13,14) was present; however, the tumor size in group B was slightly larger compared with that in group A.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The results of the analysis, which are shown in Table I, showed that the patients' mean age was 66.6 years and that a high percentage of affected patients were female (female-to-male ratio, 1.57-7.00). Of note, in group A, the prognostic data in more recent studies (5-7) tended to be improved compared with those in earlier studies (2)(3)(4). Among the more recent studies, no significant difference between the prognostic data in groups A (5-7) and B (13,14) was present; however, the tumor size in group B was slightly larger compared with that in group A.…”
Section: Discussionmentioning
confidence: 65%
“…The implementation of diagnostic methods, including CT, US and magnetic resonance imaging to detect small-sized tumors, the development of extended radical surgery may have accounted for the abovementioned findings. The differences in the malignant potential between groups A and B may be based on the fact that the cells have different origins: True carcinosarcoma is derived from totipotent stem cells, which separately differentiate into epithelial and sarcomatous cells, while undifferentiated carcinoma is a morphological variant of carcinoma, which is transformed to exhibit sarcomatous features (4). The prognosis of patients with undifferentiated carcinoma of the gallbladder may be identical or slightly worse compared with that of patients with carcinosarcoma; however, this requires further assessment by future meta-analyses of data from patients worldwide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Однако в последние несколько десятилетий отмечается тен-денция к расширению возрастного диапазона [24,27], уже не нонсенс выявление холелитиаза в детском возрасте с частотой около 5% [12,21,30,39,40].…”
Section: факторы риска особенности клинического теченияunclassified
“…Одни авторы ЖКБ счи-тают самым распространенным среди заболеваний пищеварительной системы [14,28], другие авторы, отдавая первое место язвенной болезни, позициони-руют ЖКБ как вторую проблему в гастроэнтерологии [26]. В связи с этим, проблема ЖКБ, образно назван-ной «болезнью благополучия», является одной из наи-более актуальных для современной медицины [3,4,30,36], существенным бременем для здравоохране-ния многих стран, включая и Россию [20,39].…”
unclassified